The Late Orchid Catches the Bee: Frost Damage and Pollination Success in the Face of Global Warming in a European Terrestrial Orchid - Florian P. Schiestl; Beat A. Wartmann; Ruth Bänziger; Brigitte Györög‐Kobi; Klaus Hess; Jürg Luder; Edith Merz; Beat Peter; Max Reutlinger; Tobias Richter; Heinz Senn; Thomas Ulrich; et al. (Ecology and Evolution)
ABSTRACT Global warming changes flowering times of many plant species, with potential impacts on frost damage and their synchronization with pollinator activity. These effects can have severe impacts on plant fitness, yet we know little about how frequently they occur and the extent of damage they cause. We addressed this topic in a thermophilic orchid with a highly specific pollination mechanism, the Small Spider Orchid, Ophrys araneola RchB, in six populations in Northern Switzerland. We measured flowering time, frost damage, and fruiting success in 1250 individually marked plants during 3 years, and documented spring temperatures. Using regression models with historical climate data, we estimated past and future frost damage. In addition, we analyzed historical records of the orchid and its only verified pollinator, the solitary bee Andrena combinata in Northern Switzerland, to estimate potential desynchronization between flowering and pollinator activity due to climate change. Increased spring temperatures accelerated flowering time, and together with the number of frost days explained frost damage well. Frost damage was severe and early‐flowering plants were more likely to be damaged. Historical climate data suggested frost damage has increased in the last decades and may increase further in the future. All populations but one had very low fruit set, and plants that flowered earlier were less likely to set fruit. The historical data from between 1970 and 2019 showed a significant advance of flowering‐ and pollinator occurrence time in the last decades, but to a similar degree in orchids and bees. Our study shows that the orchid, despite being limited to warm habitats in central Europe, suffers under global warming by increased frost damage caused by earlier flowering. We did not detect an effect of accelerated flowering on desynchronization in flowering time and pollinator activity in this orchid species.